(untitled) (Practitioner Research, 2023)
English Speaking anxiety affects students’ ability to speak and learn English, and it can make it difficult for students learning a foreign language to practise or acquire spoken language skills. The purpose of this systematic review is to present a critical analysis of current studies on English speaking anxiety in English learners and strategies for overcoming it. Literature were searched in Scopus, ScienceDirect, and Eric. Key words conclude Speaking anxiety, oral anxiety, communication apprehension and strategies, etc. Journals written in English published during the previous five years were among the inclusion criteria. The PRISMA Model was used in the process. The results (N=9) revealed that methodology that most of the researches used is qualitative and mixed method. Most of participants were university students as participants, but one research’s participants were primary school students. Many strategies are suggested in these research, which are English drama classes, collaborative learning with four dimensions (motivation, explaining rubrics, skill integration, and grouping), internalisation and speaking learning surroundings, training, interpersonal engagement, self-confidence growth, mobile learning, the self-system model of motivation, social strategy, meta cognitive strategy and memory strategy. This study analyzes the relevant studies on strategies to reduce English anxiety in the past five years, and after analyzing the screened literature, it summarizes the research methods they used and the strategies they proposed to be able to reduce English speaking anxiety, which can improve the theoretical support for subsequent scholars’ studies. And it can be used by teachers to reduce their students’ English speaking anxiety and improve their English speaking skills.